Take the 2-minute tour ×
Quantitative Finance Stack Exchange is a question and answer site for finance professionals and academics. It's 100% free, no registration required.

The solution to the SDE

$dx= -kx\ dt + cx \ dW$


$x(t) = x_0 e^{(c - k^2/2)t}e^{-k W}$

with mean

$\langle x(t) \rangle = x_0 e^{(c - k^2/2)t}$

where $W(t)$ is the Wiener process.

Im looking to find the expression

$\langle [W(s) + W(t) - 2W(0)]^2 \rangle$

but am unsure of how to proceed.

Help would be appreciated.

share|improve this question
add comment

2 Answers

I would calculate it this way,

$⟨[W_s+W_t−2W_0]^2⟩=\mathbb{E}[(W_s+W_t−2W_0)^2]\\ \hspace{4cm}= \mathbb{E}[((W_s-W_0)+(W_t-W_0))^2]\\ \hspace{4cm}=\mathbb{E}[(W_s-W_0)^2]+\mathbb{E}[(W_t-W_0)^2]+2\mathbb{E}[(W_s-W_0)(W_t-W_0)] \\ \hspace{4cm}=s+t+2\mathbb{E}[W_sW_t]\\ \hspace{4cm}=s+t+2min(s,t)$

share|improve this answer
add comment

Your solution $x_t$ is wrong.

Your mean is wrong too. Note that $\mathbb{E}\left[ e^{W_t}\right] = \frac{t}{2}$.

share|improve this answer
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.